ANALISIS PSIKOLOGI EKSISTENSIAL TOKOH UTAMA DALAM NOVEL SEMESTA ANASERA KARYA HINDHIASTINAAA - Heppi Naomi Lastio Sihombing; Wahyusari, Ahada; Dwi Leoni, Tessa; Irawan, Dody; Lolita, Asri; Zaitun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the meaning of life, the meaning of suffering, and the existential vacuum experienced by the main character in the novel *Semesta Anasera* by Hindhiastinaaa, based on Viktor E. Frankl's theory of logotherapy. The study employs a qualitative approach with a descriptive research design. Data collection techniques involved reading the novel serving as the research object, identifying excerpts containing elements of Viktor E. Frankl's logotherapy, and recording data corresponding to the research indicators. Data analysis techniques included identifying data related to Viktor E. Frankl's logotherapy, classifying the data into the aspects of the meaning of life, the meaning of suffering, and the existential vacuum, and subsequently describing and drawing conclusions from the research findings. The results indicate that the main character in the novel *Semesta Anasera* by Hindhiastinaaa experiences three aspects of Viktor E. Frankl's logotherapy: the meaning of life, the meaning of suffering, and the existential vacuum. The meaning of life is identified through two indicators: specific meaning in life and responsibility toward life. The meaning of suffering is identified through the indicators of changing one's attitude toward suffering and finding meaning within suffering. The existential vacuum is identified through the indicators of boredom and existential frustration. The research findings indicate that the protagonist's psychological journey evolves from a state of existential emptiness—through the ability to find meaning in their suffering—to ultimately discovering the meaning of life, in accordance with Viktor E. Frankl's concept of logotherapy.